Bicentennial man - Columbus, Cris.; Columbia Pictures; Touchstone Pictures ([s.l.] Sony Pictures Home Entertainment, 2008)
A heartfelt story which takes us through one robot's extraordinary 200-year journey to become an ordinary man. Prepare yourself to bridge the gap between man and machine, today and tomorrow, logic and love. by the year 2005, every home will have an NDR-114, a domestic robot, designed to serve humans. Like any household appliance, like any man-made machines, NDRS are all exactly the same. All except one...There is something different about Andrew...a special spark, a unique personality, something...human.
DVD
Directed by Chris Columbus
Robun Williams.
Keywords: Feature films; Fantasy films